AML and the art of remission maintenance. (September 2021) - de Lima, Marcos; Roboz, Gail J.; Platzbecker, Uwe; Craddock, Charles; Ossenkoppele, Gert
Abstract: Relapse in acute myeloid leukemia (AML) is common, especially in older patients, and there is currently no standard of care maintenance therapy for those who achieve complete remission. Finding effective, tolerable maintenance therapy to prolong remission has been a goal for decades, but early clinical trials testing a variety of agents demonstrated disappointing results with no overall survival benefit. CC-486, an oral hypomethylating agent, was recently approved in the United States for maintenance treatment in patients with AML in first remission following chemotherapy. A number of ongoing studies are assessing various therapeutics in the maintenance setting, including other hypomethylating agents, targeted small-molecule inhibitors, monoclonal antibodies, and immunomodulators. New strategies are needed to identify patients most likely to benefit from maintenance therapy, including those for whom a preemptive approach reliant on monitoring of measurable residual disease would be advantageous. Highlights: Most AML maintenance trials have shown no significant overall survival (OS) benefit. CC-486 AML maintenance significantly increased OS of patients in remission after IC. We review agents now in clinical development for use as AML maintenance therapy.